Monoclonal Antibodies Targeting Ion Channels and Their Therapeutic Potential - Haustrate, Aurélien; Hantute-Ghesquier, Aline; Prevarskaya, Natalia; Lehen’kyi, V’yacheslav (Frontiers in Pharmacology, 2019)
Monoclonal antibodies (mAbs) represent a rapidly growing pharmaceutical class of protein drugs which becomes an important part of the precision therapy. mAbs are characterized by their high specificity and affinity for the target antigen which is mostly present on the cell surface. Ion channels are a large family of trans-membrane proteins that control ion transport across the cell membrane. They are involved in almost all biological processes in both health and disease and are widely considered as prospective targets. However, no antibody-based drug targeting ion channel has been developed so far that has progressed to clinical use. Thus, we provide a comprehensive review of the elaborated mAbs against ion channels, describe their mechanisms of action and discuss their therapeutic potential.